Broad Spectrum Antimicrobial Activity of Forest-Derived Soil Actinomycete, Nocardia sp. PB-52 - Sharma, Priyanka; Kalita, Mohan C.; Thakur, Debajit (Frontiers in Microbiology, 2016)
A mesophilic actinomycete strain designated as PB-52 was isolated from soil samples of Pobitora Wildlife Sanctuary of Assam, India. Based on phenotypic and molecular characteristics, the strain was identified as Nocardia sp. which shares 99.7% sequence similarity with Nocardia niigatensis IFM 0330 (NR_112195). The strain is a Gram-positive filamentous bacterium with rugose spore surface which exhibited a wide range of antimicrobial activity against Gram-positive bacteria including methicillin resistant Staphylococcus aureus (MRSA), Gram-negative bacteria and yeasts. Optimization for the growth and antimicrobial metabolite production of the strain PB-52 was carried out in batch culture under shaking condition. The optimum growth and the antimicrobial metabolite production by the strain PB-52 was recorded in GLM medium at 28ºC, initial pH 7.4 of the medium and incubation period of eight days. Based on polyketide synthases (PKS) and nonribosomal peptide synthetases (NRPS) gene-targeted PCR amplification, the occurrence of both of these biosynthetic pathways was detected which might be involved in the production of antimicrobial metabolite in PB-52. Extract of the fermented broth culture of PB-52 was prepared with organic solvent extraction method using ethyl acetate. The ethyl acetate extract of PB-52 (EA-PB-52) showed lowest minimum inhibitory concentration (MIC) against Staphylococcus aureus MTCC 96 (0.975 μg/ml) whereas highest was recorded against Klebsiella pneumoniae ATCC 13883 (62.5 μg/ml). Scanning electron microscopy (SEM) revealed that treatment of the test microorganisms with EA-PB-52 destroyed the targeted cells with prominent loss of cell shape and integrity. In order to determine the constituents responsible for its antimicrobial activity, EA-PB-52 was subjected to chemical analysis using gas chromatography-mass spectrometry (GC-MS). GC-MS analysis showed the presence of twelve different chemical constituents in the extract, some of which are reported to possess diverse biological activity. These results confirmed that the presence of bioactive constituents in EA-PB-52 could be a promising source for the development of potent antimicrobial agents effective against wide range of microbial pathogens including MRSA.